El Mercurio of Santiago de Chile: The World Liberal Discourse Before Russia in 1905 and 1917 [el Mercurio de Santiago de Chile: El Discurso Liberal Mundial Ante Rusia en 1905 y 1917 - Garay-Vera, C (UPV/EHU Press, 2023)
The daily newspaper El Mercurio is considered as representative of the Chilean right-wing. Thus, this article explores its critical position before the regime of the Czar in respect of 1905 events, and in the beginning of the “Russian revolution” in 1917, the latter having as result the fall of the Czar. For the authors, the afore-mentioned phenomenon is consequence of the liberal discourse and identity of the newspaper as well as of his owner, Agustín Edwards MacClure (1878-1941), in relation to the British, and the French positions. For the Chilean newspaper, the Russian Empire must be functional to Anglo-French interests on the First World War. This conflict, which is perceived as predominantly European by El Mercurio, is examined from the editorials, and the journalistic coverage of those events. Finanlly, El Mercurio has a positive idea of the supposed as-cension of liberalism in Russia, and the end of the tsarist autocracy. © 2023 Historia Contemporánea (UPV/EHU).